What We Can Learn from the Electric Field and Conductivity Measurements in Auroral Atmosphere. Issue 1 (29th January 2019) - Seran, E.; Godefroy, M.
Abstract: In this paper we present measurements of the electric field and electric conductivity of air performed with the Short Dipole Antenna (SDA) in the auroral atmosphere. The observations were carried out during two stratospheric balloon flights in the northern Sweden in winter of 2011. Two‐fold objectives were attained as the outcome of these flights and the data analysis. First aimed at understanding the mechanisms that control the electric properties of the auroral atmosphere and at estimation of some key parameters from the measured data, such as the charge and current density, the mobility of the small‐ions, their concentration and generation rate, as well as the radiation dose rate. Second objective was to test the SDA instrument performances in a radiation environment close to that we expect to encounter near the Mars surface. Key Points: Understanding the mechanisms that control the electric properties of the auroral atmosphere Test the instrument performances in a radiation environment close to that we expect to encounter near the Mars surface